Propuesta de modificación del artículo 38° de la ley N° 29973 ley general de la persona con discapacidad, respecto del derecho humano de acceso y permanencia de las personas con discapacidad a las instituciones públicas de educación superior universitaria - Dueñes Chávez, Leidy Lizbeth (2017)
The present research is a political proposal on public university education, based on proposing the amendment of Article 38 of the General Law on Disability Act No. 29973; seeking to specify its content and to take care of the income (increase its number), permanence and successful graduation of students with disabilities from university classrooms. Since education is a fundamental right, it must be guaranteed to all people, and given the vulnerable situation of students with disabilities, this project formulates as a research problem to verify the need to expand the article, as a political measure of university educational inclusion to ensure the full enjoyment of the right to an education, based on the principles of Non-discrimination and Equal Opportunities. The present research is qualitative, and it was proposed to describe the determinant educational, political and social factors that in some way limit and impede the entry, stay and discharge of young disabled people, and prevents them from enjoying quality university education. Students with disabilities enrolled using payment exemption of disability signing up fees, as prescribed by the General Law of the Person with Disabilities, is the study sample. The population coincides with the sample: all disabled students enrolled using the exemption from enrollment fees, as prescribed by the General Law of the Person with Disabilities. It is a descriptive study that aims, through the collection of data, to know and assess the situation of students with disabilities enrolled in the National University of Trujillo